2015
DOI: 10.1149/2.1141509jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Extraction of Cerium by Forming Ce-Zn Alloys in LiCl-KCl Eutectic on W and Liquid Zn Electrodes

Abstract: The electrochemical formation of Ce-Zn alloys in LiCl-KCl eutectic was systematically investigated by cyclic voltammetry (CV), square wave voltammetry (SWV) and open circuit chronopotentiometry (OCP). Due to the decrease of Ce activity in the metal phase of formed Ce-Zn alloys, the deposition potential of Ce(III) at a liquid Zn electrode was found to be 0.64 V more positive than that on an inert W electrode. The co-reduction behaviors of Ce(III) and Zn(II) ions were also studied in LiCl-KCl eutectic. Signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…1a. The well-known reduction peak of cerium(III) was observed at −2.02 V 21 . Concentration of cerium(III) in all the experiments was adjusted to be 1.0 ± 0.2 wt%.…”
Section: Resultsmentioning
confidence: 95%
“…1a. The well-known reduction peak of cerium(III) was observed at −2.02 V 21 . Concentration of cerium(III) in all the experiments was adjusted to be 1.0 ± 0.2 wt%.…”
Section: Resultsmentioning
confidence: 95%
“…For example, the electrode area is changeless, and the diffusion of deposited metal into the liquid metal is easier. 6,7 Thus, liquid Ga, [7][8][9][10][11] Bi, [12][13][14][15] Cd, 13,16 Zn, [17][18][19][20][21][22][23][24] Sn 25 were selected as cathode to separate REs from molten salts. The melting point of Pb metal is 600 K and boiling point is 1798 K, it is easy to melt but doesn't evaporate at 723-823 K. Thus, Pb metal seems to be a good candidate as the cathode material in separation and extraction of REs by molten salt electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…14 Thus, liquid cathode is paid more attention because of its complete physical separation between the metal product and electrolyte, constant electrode area, and easy diffusion of deposited metal into liquid metal. Low melting metal and alloy, for example, Bi, [30][31][32] Sn, 33,34 Cd, 35,36 Pb, [37][38][39] Ga, 40,41 Zn 14,[42][43][44] metals and Al-Ga alloy [45][46][47] were explored as a liquid cathode. The feasibility of liquid metals (Sb, Bi, Pb, Sn, Ga) as cathode was systematically investigated in molten fluorides, Gibilaro et al found that the electroactivity domains and reactivity of liquid metals are Bi > Pb > Sn > Sb > Ga. 48 Lebedev 49 evaluated the separation factor between actinides and lanthanides on various cathodes in molten chlorides, and found that the separation order is Al > Ga > Pb > Zn > Bi > Sn > In > Cd > Tl.…”
mentioning
confidence: 99%